Implementasi Green Human Resource Practices dan Metode Menerapkan Praktik SDM Hijau untuk Mengurangi Jejak Karbon dalam Industri - Rajagukguk, Frederick Rudy Sentosa; Harahap, Hastuti Handayani; Arifin, Indra Welly (Economic Development Progress, 2024)
This research is about the Implementation of Green Human Resource Practices and Methods of Implementing Green Human Resource Practices to Reduce Carbon Footprints in Industry. Quantitative methods with PLS-SEM are the right approach for research on GHRP and reducing carbon footprints. PLS-SEM allows analysis of complex variable relationships, while SmartPLS makes it easier to analyze structural models. Through this approach, researchers can evaluate the effectiveness of each GHRP practice and provide appropriate recommendations for companies in reducing their carbon footprint. This study emphasizes the importance of HR's role in a company's environmental strategy. By implementing GHRP, companies can create a more environmentally conscious workforce that is actively involved in efforts to reduce carbon impact. Green training in particular makes a major contribution, as it helps employees understand and implement environmentally friendly practices in their daily work.